Electrospun, Oriented, Ferromagnetic Ni1-xFex Nanofibers - Bhugra, Vaibhav S.; Hughson, Fraser R.; Williams, Grant V. M.; Chong, Shen V.; Nann, Thomas (Frontiers in Chemistry, 2020)
Electrospinning has been used to fabricate ferromagnetic Ni0.47Fe0.53 nanofibre mats that were composed of individual, orientated Ni0.47Fe0.53 nanofibres. The key steps were processing a polyvinylpyrrolidone nanofibre template containing ferric nitrate and nickel acetate metal precursors in Ar at 300 ºC and then 95% Ar : 5% H2 at 600 ºC. The Ni0.47Fe0.53 fibres were nanostructured and contained Ni0.47Fe0.53 nanocrystals with average diameters of ~14 nm. The Ni0.47Fe0.53 ferromagnetic mats had a high saturation magnetic moment per formula unit that was comparable to those reported in other studies of nanostructured Ni1-xFex. There is a small spin-disordered fraction that is typically seen in nanoscale ferromagnets and is likely to be caused by the surface of the nanofibres. There was an additional magnetic contribution that could possibly stem from a small Fe1-zNizO phase fraction surrounding the fibres. The coercivity was found to be enhanced when compared with the bulk material.